Prediction of Survival With Long‐Term Disease Progression in Most Common Spinocerebellar Ataxia. Issue 8 (18th June 2019) - Diallo, Alhassane; Jacobi, Heike; Cook, Arron; Giunti, Paola; Parkinson, Michael H.; Labrum, Robyn; Durr, Alexandra; Brice, Alexis; Charles, Perrine; Marelli, Cecilia; Mariotti, Caterina; Nanetti, Lorenzo; et al.
Abstract: Background: Spinocerebellar ataxias are rare dominantly inherited neurodegenerative diseases that lead to severe disability and premature death. Objective: To quantify the impact of disease progression measured by the Scale for the Assessment and Rating of Ataxia on survival, and to identify different profiles of disease progression and survival. Methods: Four hundred sixty‐two spinocerebellar ataxia patients from the EUROSCA prospective cohort study, suffering from spinocerebellar ataxia type 1, spinocerebellar ataxia type 2, spinocerebellar ataxia type 3, and spinocerebellar ataxia type 6, and who had at least two measurements of Scale for the Assessment and Rating of Ataxia score, were analyzed. Outcomes were change over time in Scale for the Assessment and Rating of Ataxia score and time to death. Joint model was used to analyze disease progression and survival. Results: Disease progression was the strongest predictor for death in all genotypes: An increase of 1 standard deviation in total Scale for the Assessment and Rating of Ataxia score increased the risk of death by 1.28 times (95% confidence interval: 1.18–1.38) for patients with spinocerebellar ataxia type 1; 1.19 times (1.12–1.26) for spinocerebellar ataxia type 2; 1.30 times (1.19–1.42) for spinocerebellar ataxia type 3; and 1.26 times (1.11–1.43) for spinocerebellar ataxia type 6. Three subgroups of disease progression and survival were identified for patients with spinocerebellar ataxia type 1: "severe" (n = 13; 12%), "intermediate" (n = 31; 29%), and "moderate" (n = 62; 58%). Patients in the severe group were more severely affected at baseline with higher Scale for the Assessment and Rating of Ataxia scores and frequency of nonataxia signs compared to those in the other groups. Conclusion: Rapid ataxia progression is associated with poor survival of the most common spinocerebellar ataxia. Theses current results have implications for the design of future interventional studies of spinocerebellar ataxia. © 2019 International Parkinson and Movement Disorder Society